What do we know about the future of food demand, production, and food security based on IMPACT model projections? - Cenacchi, Nicola; Sulser, Timothy B.; Mishra, Abhijeet (International Food Policy Research Institute, 2025)
Global food demand is projected to increase as incomes rise, and diets will continue shifting toward more nutrient-dense foods, especially in low- and middle-income countries (LMICs).